Work Life Balance As A Gig Worker Some Stories Colege Student - Aiswara Denisya Ramadhani; Andriany, Lussia Mariesti (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The phenomenon of gig workers has created new flexible, project-based work patterns, attracting university students to participate. Students experience dual roles: worker and student, while remaining tied to the demands of social life, forming a triadic pattern in their daily lives. This study aims to understand how student-gig workers navigate the balance between academic, work, and social roles. Background Problems: Students' involvement in flexible work presents a unique challenge in the form of conflicts between academic, work, and social responsibilities. This phenomenon raises a key question: how do gig worker students achieve work-life balance when they simultaneously fulfill these triadic roles? Novelty: The novelty of this research lies in its focus on the context of student-gig workers in Indonesia, which is underexplored. This study not only describes students' triadic roles but also explores their strategies in negotiating role boundaries through a narrative approach that emphasizes lived experiences. Research Methods: This study used a qualitative approach with an exploratory narrative design. Data were collected through in-depth narrative interviews with five gig worker students in October and November 2025. Participants were selected purposively based on a variety of occupations, and data analysis was conducted using the Gioia methodology to trace the conceptualization process from empirical experiences to key themes. Finding/Results: The results show that gig worker students achieve a life balance through ongoing negotiations between academic demands and flexible work. They develop time management strategies, maintain intrinsic motivation, and engage in emotional adaptation in the face of role pressures. Conclusion: Gig worker students' life balance is shaped by self-awareness and adaptive skills in managing role boundaries between the triadic roles. These findings emphasize the importance of institutional support and more welcoming work policies for flexible student workers to maintain mental health, motivation to learn, and long-term work productivity.